SOCIODEMOGRAPHIC AND COMORBIDITY PROFILES OF MIGRAINE PATIENTS: AN OUTPATIENT-BASED STUDY IN A TERTIARY CARE HOSPITAL - BANDAY, MUDDASIR; WANI, MAQBOOL; FAROOQ, UMER; PARRA, BILAL; RATHER, YOUNIS (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Migraine is a primary headache disorder. The study was undertaken to assess correlation between sociodemographic characteristics of migraineurs with their various comorbidities so as to determine most important factors influencing their comorbidity profile. Methods: A prospective study was conducted between June 2018 –April 2020 in 323 patients suffering from migraine in out-patient department of Neurology. Patients were labeled as migraine on the basis of Simplified Diagnostic Criteria for Migraine. A structured questionnaire was used for evaluation of sociodemographic variables and evidence based approach was adapted to fill psychiatric and comorbidity profiles of patients. Results: In 323 patients of migraine males were 30 (9.3%) and females 293 (90.7%). Mean age of males is 38.80±17.53 years and of females 35.38±13.29 years, (p=0.307). Most of them were in 21-30 years age group followed by 31-40 years Majority of patients were from district Srinagar followed by Ganderbal. Housewives formed major group of patients followed by students It was seen more in the illiterate class than in literates. 57% patients belonged to lower middle class. Psychiatric comorbidities including anxiety,depression and physical comorbidities like hypertension, hypothyroidism and comorbid pains were common associations. Comorbidities have been compared with mean age of the patients and it was found that psychiatric comorbidities, neuropathic pain, hypothyroidism, hypertension, Type 2 DM, comorbid pains and PCOD were statistically significant, (p=≤0.05). Conclusion: Most common comorbidities associated with migraine are anxiety, depression, neuropathic pain, hypothyroidism, hypertension, Type 2 DM and comorbid pain. Comorbidities have direct impact on nature of treatment protocol and need to be addressed to achieve outcome based treatment.